Effects of velocity based training vs. traditional 1RM percentage-based training on improving strength, jump, linear sprint and change of direction speed performance: A Systematic review with meta-analysis - Liao, K.-F.; Wang, X.-X.; Han, M.-Y.; Li, L. L.; Nassis, G. P.; Li, Y.-M. (PLOS ONE, 2021)
Background: There has been a surge of interest on velocity-based training (VBT) in recent years. However, it remains unclear whether VBT is more effective in improving strength, jump, linear sprint and change of direction speed (CODs) than the traditional 1RM percentage-based training (PBT). Objectives: To compare the training effects in VBT vs. PBT upon strength, jump, linear sprint and CODs performance. Data sources: Web of science, PubMed and China National Knowledge Infrastructure (CNKI). Study eligibility criteria: The qualified studies for inclusion in the meta-analysis must have included a resistance training intervention that compared the effects of VBT and PBT on at least one measure of strength, jump, linear sprint and CODs with participants aged =16 yrs. and be written in English or Chinese. Methods: The modified Pedro Scale was used to assess the risk of bias. Random-effects model was used to calculate the effects via the mean change and pre-SD (standard deviation). Mean difference (MD) or Standardized mean difference (SMD) was presented correspondently with 95% confidence interval (CI). Results: Six studies met the inclusion criteria including a total of 124 participants aged 16 to 30 yrs. The differences of training effects between VBT and PBT were not significant in back squat 1RM (MD = 3.03kg; 95%CI: -3.55, 9.61; I2 = 0%) and load velocity 60%1RM (MD = 0.02m/s; 95%CI: -0.01,0.06; I2 = 0%), jump (SMD = 0.27; 95%CI: -0.15,0.7; I2 = 0%), linear sprint (MD = 0.01s; 95%CI: -0.06, 0.07; I2 = 0%), and CODs (SMD = 0.49; 95%CI: -0.14, 1.07; I2 = 0%). Conclusion: Both VBT and PBT can enhance strength, jump, linear sprint and CODs performance effectively without significant group difference.